DFT study of adsorption and diffusion of atomic hydrogen on metal surfaces - Gómez, Elizabeth del Valle (2017)
An extensive study of adsorption and diffusion of hydrogen atoms on (100) surfaces of fcc Au, Cu, Ag and Pt was performed by means of DFT calculations. Bulk properties of those metals were calculated and compared with previous results. The adsorption distances and energies of the hydrogen atom on top, hollow and bridge sites of the (100) surfaces were calculated in order to elucidate preferential adsorption sites of hydrogen on each metal. All these calculations were done in conjunction with a study of charge distribution. Finally, diffusion of the H atom from the most stable adsorption site to the nearest neighbouring site was studied in order to obtain diffusion barrier and diffusion velocity values. The highest diffusion velocity was found to be v=6.44×1011 s−1 for the case of Ag, whereas the lowest was v=1.13×107 s−1 for Au.